2010
DOI: 10.1007/s00540-009-0860-2
|View full text |Cite
|
Sign up to set email alerts
|

Can intravenous atropine prevent bradycardia and hypotension during induction of total intravenous anesthesia with propofol and remifentanil?

Abstract: This study was conducted to examine whether pretreatment with intravenous atropine could prevent bradycardia and hypotension during induction of total intravenous anesthesia with propofol and remifentanil in a prospective randomized placebo-controlled manner. Seventy patients, aged 24-78 years, were randomly divided into two groups, and received 0.5 mg atropine or placebo saline 1 min before induction of intravenous anesthesia with remifentanil at 0.4 microg/kg/min, propofol at a target blood concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Even if induction drugs do not provoke bradycardia, they can have important effects on the circulation by inducing vasodilatation as is the case for propofol,58 59 thiopental58 60 and for the opiates morphine,61 sufentanyl62 and remifentanil 63…”
Section: Mechanisms Of Bradycardiamentioning
confidence: 99%
See 1 more Smart Citation
“…Even if induction drugs do not provoke bradycardia, they can have important effects on the circulation by inducing vasodilatation as is the case for propofol,58 59 thiopental58 60 and for the opiates morphine,61 sufentanyl62 and remifentanil 63…”
Section: Mechanisms Of Bradycardiamentioning
confidence: 99%
“…A recent study in adults shows a fall in blood pressure during propofol anaesthesia due to vasodilatation despite atropine use, notwithstanding conservation of the heart rate 59. It is important to bear in mind that there are no similar studies in intensive care to determine if atropine maintains perfusion during intubation where cardiac output and vascular resistance are already compromised.…”
Section: Clinical Studies and Side Effects Of Atropinementioning
confidence: 99%
“…Various studies have reported bradycardia and even asystole after use of newer induction agents especially Propofol, Vecuronium and Fentanyl 2,7,8 , but in our study bradycardia was not encountered after use of these drugs (before carboperitoneum creation) probably that was countered by catecholamine surge after airway manipulation. Bradycardia in fourteen patients (30%) presented for laparoscopic surgery after carboperitoneum creation along with use of vagotonic drugs is alarming and careful haemodynamic monitoring and prophylactic management with Atropine sulphate should be considered to minimize morbidities.…”
Section: Discussionmentioning
confidence: 49%
“…Maruyama K et al used 0.5 mg Atropine sulphate prophylactically to assess bradycardia and hypotension during Propofol, Vecuronium and Ramifentanyl anaesthesia and found that Atropine sulphate could prevent bradycardia but not hypotension during that combination anaesthesia 7 . Takashi H et al reported that Propofol induced bradycardia is diffi cult to treat with higher doses of Atropine as well 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Propofol enhances parasympathetic activity, which can explain the bradycardia often observed after induction of anesthesia. In adults, the decrease in heart rate after propofol in patients who were also receiving a continuous infusion of remifentanil was abolished by pretreatment with 0.5 mg IV atropine [ 168 ]. Since cardiac output depends to a large extent on heart rate in neonates, a bradycardia will compromise the cardiac output and decrease tissue oxygenation.…”
Section: Anesthetic Agents For Rsimentioning
confidence: 97%